2009
DOI: 10.1002/gps.2350
|View full text |Cite
|
Sign up to set email alerts
|

The effects of reminiscence therapy on psychological well‐being, depression, and loneliness among the institutionalized aged

Abstract: Objectives: To examine the effects of reminiscence therapy on psychological well-being, depression, and loneliness among institutionalized elderly people. Methods: In an experimental study design, 92 institutionalized elderly people aged 65 years and over were recruited and randomly assigned to two groups. Those participants in the experimental group received reminiscence therapy eight times during 2 months to examine the effects of this therapy on their psychological well-being. Results: After providing the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
199
5
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 256 publications
(228 citation statements)
references
References 38 publications
14
199
5
10
Order By: Relevance
“…Only one study examining an outcome of loneliness was found (Chiang et al, 2010). Two studies examining anxiety (Emery, 2002;Haslam et al, 2010) and eight studies examining depression (Chao et al, 2006;Chiang et al, 2010;Chueh & Chang, 2014;Emery, 2002;Haslam et al, 2010;Karimi et al, 2010;Stinson & Kirk, 2006;Wilson, 2006) were identified. Three studies measured more than one outcome (Chiang et al, 2010;Emery, 2002;Haslam et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only one study examining an outcome of loneliness was found (Chiang et al, 2010). Two studies examining anxiety (Emery, 2002;Haslam et al, 2010) and eight studies examining depression (Chao et al, 2006;Chiang et al, 2010;Chueh & Chang, 2014;Emery, 2002;Haslam et al, 2010;Karimi et al, 2010;Stinson & Kirk, 2006;Wilson, 2006) were identified. Three studies measured more than one outcome (Chiang et al, 2010;Emery, 2002;Haslam et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies examining anxiety (Emery, 2002;Haslam et al, 2010) and eight studies examining depression (Chao et al, 2006;Chiang et al, 2010;Chueh & Chang, 2014;Emery, 2002;Haslam et al, 2010;Karimi et al, 2010;Stinson & Kirk, 2006;Wilson, 2006) were identified. Three studies measured more than one outcome (Chiang et al, 2010;Emery, 2002;Haslam et al, 2010). Of the eight studies, three studies were from the United States of America (USA) (Emery, 2002;Stinson & Kirk, 2006;Wilson, 2006), three studies were from Taiwan (Chao et al, 2006;Chiang et al, 2010;Chueh & Chang, 2014), one study from the United Kingdom (UK) (Haslam et al, 2010), and one study from Iran (Karimi et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations